PENGALAMAN SHARENTING DI INSTAGRAM SEBAGAI UPAYA PRESENTASI DIRI PADA IBU MILENIAL - Devina Meidy Fidelia Putri Pangudi; Triyono Lukmantoro; Amida Yusriana (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
This study aims to explore how millennial mothers perceive and engage in sharenting, specifically on the Instagram platform, focusing on self-presentation. Drawing on symbolic interaction theory and self-presentation theory, in-depth interviews were conducted with eligible millennial mothers. The data was analyzed using Interpretative Phenomenological Analysis (IPA). The findings highlight that millennial mothers intentionally select and present symbolic elements through Instagram features like editing tools, feed, story, filter, caption, and background music to convey aspects of self-identity. This process is closely intertwined with audience interaction. Furthermore, mothers place significant emphasis on the content they share, prioritizing positivity and educational value. This selective approach aligns with self-presentation strategies, including ingratiation, self-promotion, and exemplification. These strategies collectively contribute to positive audience impressions, portraying harmonious family dynamics, demonstrating parental competence, and reflecting integrity and moral values. The research suggests that millennial mothers find value in utilizing Instagram for sharenting, strategically creating positive impressions to support their roles as parents. While sharenting offers numerous benefits, it is important to acknowledge potential emotional impacts on mothers. This study also indicates that sharenting will continue to be a significant aspect of millennial motherhood. This underscores the importance of deeper understanding and digital literacy education in the community.